A strategy to synthesize pomegranate‐inspired hollow mesoporous molecularly imprinted nanoparticles by organic‐organic self‐assembly of dopamine. Issue 2 (20th November 2020) - Ji, Shunli; Huang, Jiawen; Li, Tengfei; Luo, Xi; Zheng, Feng
Abstract: Molecularly imprinted polymers (MIPs) have attracted tremendous attention as potential materials, but the conventional MIPs preparation limits its application. In this study, a novel strategy to synthesize pomegranate‐inspired hollow mesoporous molecularly imprinted nanoparticles (HMMINs) by organic‐organic self‐assembly of dopamine is reported. Benefiting from the unique chemical composition and architecture, the one‐pot synthesized HMMINs not only provide high imprinting efficiency and binding capacity, but possess biocompatibility, photothermal (PT) and sustained release effect, which indicates HMMIPDAs have great potential to be applied as a sorbent to increase the selectivity of analytes from complex matrices, and drug carrier for PT therapy to achieve sustained‐release of the drug. Abstract : Pomegranate‐inspired hollow mesoporous molecularly imprinted nanoparticles were prepared by a one‐pot synthesis method as a sorbent to increase the selectivity of analytes from complex matrices, and drug carrier for PT therapy to achieve sustained‐release of the drug.